The role of carious lesions in the occurrence of pathological modifications in deep periodontal level - radiographic evaluation - Lazăr Ana Petra; Vlasa Alexandru; Csilla Bukhari; Imola Buka; Lazăr Luminița ("George Emil Palade" University of Medicine, Pharmacy, Science, and Technology of Targu Mures, 2019)
In the etiology of periodontal disease, dental caries act as a favoring factor. The purpose of our study was to evaluate the role of untreated or incorrectly treated carious lesions in the occurrence of pathological changes in the periodontal support. Material and methods: In order to evaluate the impact of the dental caries in the appearance of destructive lesions at the periodontal level, we examined 378 X-rays. The radiographies were selected based on the presence of approximal dental cavities, untreated or incorrectly treated and we appreciated the association of these factors with the presence and the level of bone resorption of the interdental septum. Results: On the 378 radiographies we examined, it was discovered the presence of 398 approximal carious lesions, of which 146 were associated with bone resorption. The examined radiographies permitted us to evaluate 1512 fillings inserted in second class cavities, of which 1103 were correctly done, and 309 were incorrect and associated with bone resorption phenomena. Incorrectly done restorations were associated with bone resorption phenomena due to the lack of contact with the adjacent tooth for 213 of these, and because of an inaccurate adaptation at the level of the gingival threshold for 96. Conclusions: The dentist has to pay a special attention to the approximal coronary restorations because these can favor the retention of bacterial plaque and, in most cases, can lead to bone loos in the alveolar ridge area.